Repair of complete atrioventricular canal defects: Early and midterm results and comparison of the left anterior leaflet augmentation technique with traditional technics - Basgoze, Serdar; Yildiz, Okan; Ozturk, Erkut; Onan, Ismihan Selen (WILEY, 2021)
Background Complete atrioventricular septal defects (CAVSD) include a variable spectrum of congenital malformations with different forms of clinical findings. We examined early and midterm outcomes, the need for reoperation, postoperative residual AV valve regurgitation, and other risk factors after various CAVSD repairs. Methods Between 2014 and 2018, we have performed 89 isolated CAVSD repairs. We retrospectively reviewed the patients' medical records. Patients were divided into three groups according to their repair techniques modified one patch repair (MP) (n = 16)

two patch repair (TP) (n = 49)

and left anterior leaflet augmentation (ALA) technique (n = 24). Results Eighty patients (89.8\%) survived hospital discharge. Early mortality rates were three (18.8\%) in the group MP, five (10.2\%) in the group TP, and one (4.2\%) in the group ALA. Thirteen patients died during the follow-up period. Late mortality rates were three (18.8\%) in the group MP, four (16.6\%) in the group ALA, and six (12.2\%) in the group TP. The mean follow-up time was 35.9 +/- 22.97 months (range: 0.3-77 months). The morbidity and mortality results were similar between-group TP and ALA but worse in the MP group. Low body weight (<4 kg) and younger age at surgery (<4 months) were found to be risk factors on mortality by univariate and multivariate analysis. Surgical technic was not found to be an independent risk factor. Conclusion In our series, TP and ALA techniques had satisfactory results in early and midterm periods. Younger age and small bodyweight might increase early mortality and the need for reoperation.
Keywords: anterior leaflet augmentation; complete atrioventricular septal defects; congenital cardiac surgery; modified one patch; two patch